1984
DOI: 10.1002/1097-0142(19840301)53:5<1137::aid-cncr2820530520>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma carcinoembryonic antigen and acinar cell carcinoma of the pancreas

Abstract: Seventeen patients with histologically proven pancreatic cancers were studied in order to clarify the relationship of histologic types to plasma carcinoembryonic antigen (CEA) values. Two cases with marked elevation of plasma CEA values having 6100 ng/ml and 2500 ng/ml, respectively, disclosed histologically acinar cell carcinoma and mixed acinar and ductal cell carcinoma, respectively. Despite of massive hepatic metastases, the other 15 cases with ductal cell carcinoma, including 3 cases with cystadenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Our in vivo model of human PACC can provide a novel means to further investigate the genetic and cellular mechanisms of this disease. Hence, we confirmed that the PDTX tumors were composed of human acinar cell carcinoma cells via STR profile, corroboration of biomarker expression seen in PACC patient tissues [ 15 18 ] and secretion of lipase into the bloodstream [ 14 , 48 ] (Additional file 1 : Table S1; Figs. 1 , 3 ).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our in vivo model of human PACC can provide a novel means to further investigate the genetic and cellular mechanisms of this disease. Hence, we confirmed that the PDTX tumors were composed of human acinar cell carcinoma cells via STR profile, corroboration of biomarker expression seen in PACC patient tissues [ 15 18 ] and secretion of lipase into the bloodstream [ 14 , 48 ] (Additional file 1 : Table S1; Figs. 1 , 3 ).…”
Section: Discussionsupporting
confidence: 76%
“…1 c, panels i–iii). PA-018 also expressed previously documented markers of PACC, including CEA [ 15 ], CK18 [ 16 ] and BCL10 [ 17 , 18 ] (Fig. 1 c, panels iv, vi) and had a lack of cytokeratin 19 (CK19) expression, a marker of ducts and pancreatic ductal tumors [ 23 ] (Fig.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Patients usually present only non-specific symptoms (Klimstra et al 1992), but in some cases, lipase produced by the tumour cells may cause arthralgia and subcutaneous fat necrosis (Robertson & Eeles 1970;Burns et al 1974;Radin et al 1986). Analysis of common tumour markers in serum usually gives negative results (Klimstra et al 1992), but elevated concentrations of alpha-fetoprotein (Le Borgne et al 1989;Ztoh et al 1992;Kawamoto et al 1992;Nojima et al 1992) and carcinoembryonic antigen have occasionally been reported (Horie et al 1984). Elevated concentration of elastase-1 has been reported in serum in one case (Zshihara et al 1989).…”
mentioning
confidence: 99%
“…Immunohistochemical positivity in ACC has been reported mainly for trypsin, but also for chymotrypsin, lipase, α‐1‐antitrypsin, cytokeratin, lysozyme and rarely for amylase [1,2,5,13,14]. In addition, ACC can show positivity for various tumour markers such as alpha‐fetoprotein [15], carcinoembryonic antigen [15,16] and CA 19–9 [15].…”
Section: Discussionmentioning
confidence: 99%